Business Design Of Public Electric Vehicle Charging Stations For Trans Java Cikampek – Surabaya Toll With The Dynamic System Approach - Willy Novananda Novananda Siregar; Eri Prabowo (Jurnal IPTEK, 2023)
Government support through Presidential Regulation No. 55 of 2019 concerning the Acceleration of the Battery-Based Electric Motor Vehicle Program for Road Transportation and the Ministry of Energy and Mineral Resources which has issued Ministerial Regulation No. 13 of 2020 concerning the Provision of Electric Charging Infrastructure for Battery-Based Electric Motorized Vehicles. The Ministerial Regulation explains that the government aims to accelerate the battery-based Electric Motorized Vehicle (KBL) program. This regulates the electric charging facility for KBL.The Public Electric Vehicle Charging Station (SPKLU) is a business opportunity that can provide benefits for producers and national business entrepreneurs. This study reviews the business opportunities for public electric vehicle charging stations, especially on the Trans Java Cikampek Surabaya Toll Road, using a dynamic system approach. Several reviews were also discussed which included emission conversions, business schemes, financial analysis, and investment values. In this paper, there isan option for placing the SPKLU on the Trans Java Cikampek – Surabaya 54 rest area as a business opportunity for business actors to invest in SPKLU.Financial analysis regarding the feasibility of SPKLU investment, can provide investment certainty regarding the business model of providing SPKLU with the Ultra Fast Charging Out Door type